The Hydrogen and Sulfur Surfaces Effect on the Structural and Electronic Properties of Graphene Nano Ribbon - Huda Bukheet Hassan (Journal of Global Pharma Technology, 2018)
Present work deals with the effect of hydrogen and sulfur surfaces on the structural and electronic properties of grapheme nano-ribbon using the B3LYP/DFT with 6-31G basis sets .Employed at the Gaussian 09 package of programs. The results showed suitable basis functions used to describe each GNR gave good relaxation and structural properties. The total energy was decreased when increasing the number of atoms in the structure. The LUMOs are greater than HOMOs in which these GNRs have the ability to donating or accepting electrons .The presence of the surfaces in the GNR increases the energy gap of the NR. For all structures, the IP is larger than the EA, means these GNRs need small energy to acceptance an electron and becomes anions. All GNRs have high electronic softness.Keywords: HOMO, LUMO, B3LYP, Softness and Hardness.